MOA-2020-BLG-208Lb: cool sub-Saturn-mass planet within predicted desert - Olmschenk, Greg; Bennett, David P.; Bond, Ian A.; Zang, Weicheng; Jung, Youn Kil; Yee, Jennifer C.; Bachelet, Etienne; Abe, Fumio; Barry, Richard K.; Bhattacharya, Aparna; Fujii, Hirosane; Fukui, Akihiko; et al. (The astronomical journal, 2023)
We analyze the MOA-2020-BLG-208 gravitational microlensing event and present the discovery and characterization of a new planet, MOA-2020-BLG-208Lb, with an estimated sub-Saturn mass. With a mass ratio , the planet lies near the peak of the mass-ratio function derived by the MOA collaboration and near the edge of expected sample sensitivity. For these estimates we provide results using two mass-law priors: one assuming that all stars have an equal planet-hosting probability, and the other assuming that planets are more likely to orbit around more massive stars. In the first scenario, we estimate that the lens system is likely to be a planet of mass and a host star of mass , located at a distance . For the second scenario, we estimate , , and . The planet has a projected separation as a fraction of the Einstein ring radius . As a cool sub-Saturn-mass planet, this planet adds to a growing collection of evidence for revised planetary formation models.
Gesehen am 13.11.2023